BIMBINGAN BELAJAR SEBAGAI PROGRAM PEMULIHAN PENDIDIKAN PADA MASA PANDEMI COVID-19 DI DESA NGAYUNG - Arezqi Asmana; Abdur Rohim; Muhammad Kurniawan; Ahsanul Kholiqin; Nur Laili (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
The impact of the Covid-19 pandemic since two years ago has made the world of education adapt to various changes. One of the programs implemented by UNISDA KKN to overcome problems arising from the Covid-19 pandemic in Ngayung Village, Maduran District, Lamongan Regency is Tutoring for Children. The Tutoring Movement is aligned with the National Movement for National Character Education. The aim is to inspire children about the importance of science through tutoring programs. This program encourages and motivates children to be creative, innovative and confident in their abilities. By doing this, children will be enthusiastic to participate in activities related to learning and show changes in students who generally experience problems.